Social and Legal Determinants of Informal Marriages in Mananggu District - Narti Husain; Nirwan Junus (Damhil Law Journal, 2025)
The phenomenon of informal marriages in various regions of Indonesia, including Mananggu District in Boalemo Regency, continues to persist despite legal regulations that mandate marriage registration, as stipulated in Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 concerning Marriage. This study aims to analyze the factors influencing the prevalence of unregistered marriages and examine the social and legal impacts from the perspective of legal sociology. The research method employed is an empirical legal approach with field studies, including in-depth interviews with community leaders, religious affairs office staff, couples involved in informal marriages, and secondary data analysis from regulations, legal literature, and previous research findings. The study finds that several key factors contribute to the high rate of informal marriages, including social factors (out-of-wedlock pregnancies, customary pressures, and religious legitimacy), cultural factors (the belief that a marriage is legitimate based on Islamic law without state registration), economic factors (administrative costs and access to transportation to the religious affairs office), and administrative factors (complexity of document processing). The impacts are significant, both legally and socially. Legally, the wife and children lose legal protection for basic rights such as maintenance, inheritance, and civil status. Socially, negative stigma, vulnerability to discrimination, and barriers to accessing education and public services arise. In conclusion, informal marriages present a multidimensional problem that requires legal, administrative, and social solutions to ensure the protection of citizens' rights.